Penciptaan Tari Rambasaka Kabokemu Ikatan Perempuan yang Ingin Lepas dari Tindakan KDRT - Waode Muriani Ekasari Virno Bolu (Departement of Mathematics Education, 2023)
In Butonese, untying is rambasaka kabokemu. The dance work's choreography is inspired by criticism of the phenomenon of violence against women. The rise of the issue of violence against women makes dancers reveal the other side of women who are trying to break free from shackles. Rambasaka Kabokemu is danced by male and female dancers who depict an abusive relationship with visual media forms. The creation method used in this work is